การวิเคราะห์ความเสียหายของโครงข้อแข็งคอนกรีตเสริมเหล็ก 2 มิติเนื่องจากการทรุดตัวของฐานรองรับ - อรรถวิทย์ จงใจวาณิชย์กิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This research develops a computer program for nonlinear analysis of R/C frames subjected to various loading, uniformly-distributed loading, such as joint loading, and support settlement. Both material nonlinearity of R/C sections and geometrical nonlinearity are included. Newton-Raphson method is used for nonlinear analysis and the convergence of results is accomplished by specifying a tolerance of Euclidean norm of the residual force vector. The properties of R/C sections are modeled as a trilinear-relationship between moment and curvature assuming constant axial force. Flexibility-based macromodel, derived from spread plasticity model and yield penetration model, is adopted to calculate the stiffness of inelastic elements. Then the stiffness matrix of an inelastic structure is assembled. While geometrical nonlinearity resulted from P-Delta effect is included using a geometric stiffness matrix. From the examples, the elastic results show that the differences of displacements and support reactions are very small compared with STAAD-III. For inelastic problems, the differences of base shears at the stages of cracking and yielding of element sections are less than 4 percents compared with IDARC2D version 4.0. Moreover, comparing with the test results, there are only about 8-percent differences in ultimate load prediction. Finally, an R/C frame subjected to support settlement is evaluated. The first cracks are found in the beams on the first story. Further settlement leads to some other cracks in the first-floor columns. Therefore, it is recommended to strengthen those elements to pervent the damage of the building.